Perspectives on Barry Hannah - Bone, Martyn, 1974- (Book collections on Project MUSE., 2007)
Perspectives on Barry Hannah is a collection of essays devoted to the work of the award-winning fiction writer Barry Hannah. The anthology features a broad range of critical approaches and covers the span of Hannah's career from Geronimo Rex (1972) to Yonder Stands Your Orphan (2001). The book also includes a previously unpublished interview with Hannah. The ten essays cover all of Hannah's thirteen published books. The contributors give fresh perspectives on Hannah's classic works (Airships and Ray), provide illuminating readings of important fiction that has received less critical attention.